Image completion: Survey and comparative study - Zarif, S. (World Scientific Publishing Co. Pte Ltd, 2015)
Image completion is an active and interesting research area in image processing and computer graphics. Restoration and retouching of damaged areas in an undetectable form is the objective of image completion techniques. Most of the recently developed video completion methods are extensions of image completion techniques to restore the damaged frames. With respect to video completion challenges and image completion future work, we survey existing methods and introduce a new classification. The methods in each category are described in detail. In the second part of the paper, we provide a comparison and evaluation study between the most recent image completion methods qualitatively as well as quantitatively. For a fair comparison, we introduced a new dataset and evaluated four available image completion methods on the same hardware. Experimental results are conducted to highlight the strengths and drawbacks of each image completion method. Â© 2015 World Scientific Publishing Company.